Exploration on the influence mechanism of nitrogen doped CoO on oxygen reduction and evolution reaction in Li–O2 battery. (20th July 2022) - Gu, Xiaolei; Wang, Nan; Ma, Shiyu; Lian, Zheng; Wang, Lidan; Li, Jie; Lu, Youcai; Liu, Qingchao
Highlights: Heteroatom nitrogen affect the performance of Li–O2 batteries significantly. The discharge and charge processes are optimized with the introduction of nitrogen. Nano-sheet Li2 O2 depositing on nitrogen doped cathode benefits its decomposition. Influence mechanism of nitrogen on the battery performance was studied systematically. Abstract: Admitting that the validity of heteroatom doped transition metal oxides in improving electrochemical performances in Li–O2 battery, the reasons for the improvement remains ambiguous. In this study, nitrogen as a heteroatom is introduced to the CoO nanoneedle arrays grown on the carbon cloth (NCoO NAs/CC), and the effects of nitrogen on the electrochemical behavior of Li–O2 batteries are comprehensively studied by experimental and theoretical calculations. With the incorporation of nitrogen, the catalytic activity of the prepared cathode is heavily enhanced through a combined set of factors, including enhanced electronic conductivity, optimized reactant/intermediates affinity, as well as improved reaction kinetics. In addition, further investigation on the morphology of the discharge products demonstrates that the introduction of nitrogen can also promote the solvation discharge path of the battery, which is conducive to the release of the battery capacity. Moreover, the introduction of nitrogen makes the discharge products on the cathode show nano-sheet structure, which is easier to be decomposed during charging. The electrochemical performances of the NCoO NAs/CC cathode including battery cycle efficiency, capacity and cycle stability are heavily enhanced due to the above advantages. The combination of doping engineering and electrochemical performances provides an ingenious way to develop a new type of economic and efficient cathode for Li–O2 batteries. Graphical abstract: Image, graphical abstract